A hybrid approach to teaching physical education students the skills of managing and organizing sporting events - Golyakov I.P.; Busyreva A.S.; Gitman E.K. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to demonstrate the feasibility and efficacy of incorporating game design techniques into a blended learning approach for aspiring physical education instructors seeking to enhance their abilities in organizing children’s sports play. Methods and structure of the study. The research was conducted at the Perm State Humanitarian Pedagogical University. The study included 36 students from the Faculty of Physical Education, specializing in 44.04.05 Pedagogical Education with two profiles: «Physical Culture» and «Additional Education». The article outlines the process of developing the components of future physical education teachers’ readiness to organize children’s play activities in the context of hybrid learning. The article also presents a modified version of the game design technology as a versatile tool for the organizer of game forms. Results and conclusions. The findings of the educational experiment demonstrated a substantial superiority of the blended learning approach in acquiring the skills of game development over the conventional lecture-based instructional method.